The Six Sigma application and its impacts on the sustainability of gold scrap management procedure in small-scale jewellery industry / Saadiah Kaspin - Kaspin, Saadiah (2023)
This study aims to assess small scale jewellers' knowledge of gold waste and quality management processes. In this context, quality can be defined as a dynamic state associated with products, services, people, processes, and environments that meets or exceeds expectations and contributes to the creation of superior value. Despite the changing business landscape, the study found that most existing fabrication techniques and design methodologies are still traditional. The research focuses on small-scale industry players in Kelantan, Malaysia. The critical question is how existing fabricators and producers develop, track, and monitor their business's efficacy in performing day to-day processes, as there is a gap in the space of gold waste management processes that could result in monetary loss and have a significant impact on their financial standings. As a result, it is critical for this research to establish credibility by validating potential weaknesses and gaps, particularly in gold waste management and handling processes, and then developing the appropriate mechanism to nearer the holes.